They stole my baby's soul: narratives of embodiment and loss. Issue 2 (5th December 2005) - Campbell, A V; Willis, M
Abstract : The controversy over retained organs, arising from the Bristol and Alder Hey findings about postmortem uses of body parts, has revealed a gulf between medical and lay understandings of the human body and its relationship with the human person. There is a clear utility in having a "doctor's story", which is different from the way patients and their families understand the significance of the body, since this enables medical diagnosis and treatment to be effective. When, however, the medical narrative intrudes uncritically into areas where the key issue is the integration of the body with the person, experienced or remembered, things go badly wrong with communications in medicine. For the lay person disrespectful treatment of the body of a loved one represents a personal attack. In this respect, strong emotion, seen as irrelevant or distracting by scientific medicine, is a central aspect of the narrative concerned with loss of a loved person. For doctor and lay person alike, a narrative of the self which pays proper attention to the embodiment of the self, offers the possibility of a genuinely humane medicine.